The old success ebook - Grimes, Martha (Richard Jury, 2022)
As the New York Times –bestselling series continues, an unlikely trio of detectives teams up to solve three murders spanning three English counties. When the body of a French woman washes up on a wild inlet off the Cornish coast, Brian Macalvie, divisional commander with the Devon-Cornwall police is called in. Who could have killed this beautiful tourist, the only visible footprints nearby belonging to the two little girls who found her? While Macalvie stands stumped in the Scilly Islands, inspector Richard Jury, twenty miles away on Land's End, is at the Old Success pub, sharing a drink with the legendary former CID detective Tom Brownell, a man renowned for solving every case he undertook—well, nearly every case. Bronwell discloses that there was one he once missed. In the days following the mysterious slaying of the Parisian tourist, two other murders are called in to Macalvie and Jury's teams. First, a man is shot on a Northhamptonshire estate, then a holy duster turns up murdered at Exeter Cathedral in Devon. When Macalvie and Jury decide to consult Bronwell, the retired detective tells them that the three murders, though very different in execution, are connected. As the trio sets out to solve this puzzle, Jury and Macalvie hope that this doesn't turn out to be Brownell's second ever miss . . . "Fans of Martha Grimes will enjoy The Old Success , while newcomers will be ready to tackle her extensive body of work, which is an entertaining array of several approaches to mystery novels." — Bookreporter